2010
DOI: 10.1016/j.jempfin.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The dividend–price ratio does predict dividend growth: International evidence

Abstract: Unpredictable dividend growth by the dividend-price ratio is considered a 'stylized fact' in post war US data. Using long-term annual data from the US and three European countries, we revisit this stylized fact, and we also report results on return predictability. We make two main contributions. First, we document that for the US, results for long-horizon predictability are crucially dependent on whether returns and dividend growth are measured in nominal or real terms, and this difference is due to long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 43 publications
1
57
0
Order By: Relevance
“…Van Binswangen and Koijen (2010) use filtering techniques to highlight that dividend growth is predictable by the dividendprice ratio in the US also in the more recent past. In addition, Engsted and Pedersen (2010) provide evidence for dividend growth predictability in Denmark and Sweden. Rangvid, Schmeling and Schrimpf (2013) regard a larger cross-section of countries to show that dividend-price ratios of small countries, e.g.…”
Section: Variance Decomposition With Correlated Components: Stock Excmentioning
confidence: 90%
“…Van Binswangen and Koijen (2010) use filtering techniques to highlight that dividend growth is predictable by the dividendprice ratio in the US also in the more recent past. In addition, Engsted and Pedersen (2010) provide evidence for dividend growth predictability in Denmark and Sweden. Rangvid, Schmeling and Schrimpf (2013) regard a larger cross-section of countries to show that dividend-price ratios of small countries, e.g.…”
Section: Variance Decomposition With Correlated Components: Stock Excmentioning
confidence: 90%
“…The literature has concluded that in-sample (INS) return predictability is primarily found in the UK and US (Rapach and Wohar, 2009;Engsted and Pedersen, 2010), in developed countries (Hjalmarsson, 2010), or in the largest countries (Rangvid, Schmeling, and Schrimpf, 2011). However, only Rangvid, Schmeling and Schrimpf (2011) formally test the link between country characteristics and INS predictability.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with positive in ‡ation predictability over the period 1871-1976 as shown in Table 1. 6 We believe that these di¤erences between nominal and real return and dividend growth predictability due to in ‡ation predictability are not generally acknowledged, although emphasized by Engsted and Pedersen (2010). Whether to interpret the empirical results as evidence of predictability or unpredictability of returns and dividend growth by the price-dividend ratio naturally hinges on the underlying economic 5 According to (3) it should be future long-horizon discounted in ‡ation, returns, and dividend growth (where the discount factor is ) that are related to pd t .…”
Section: The Price-dividend Ratio and Future Returns And Dividend Growthmentioning
confidence: 99%